2011
DOI: 10.1186/1475-2891-10-77
|View full text |Cite
|
Sign up to set email alerts
|

Mn bioavailability by polarized Caco-2 cells: comparison between Mn gluconate and Mn oxyprolinate

Abstract: BackgroundMicronutrient inadequate intake is responsible of pathological deficiencies and there is a need of assessing the effectiveness of metal supplementation, frequently proposed to rebalance poor diets. Manganese (Mn) is present in many enzymatic intracellular systems crucial for the regulation of cell metabolism, and is contained in commercially available metal supplements.MethodsWe compared the effects of two different commercial Mn forms, gluconate (MnGluc) and oxyprolinate (MnOxP). For this purpose we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, it is quite important to have new iron formulations that show better safety and efficacy than standard ones. In this context, our results clearly demonstrated the safety and the trans-epithelial transported efficacy of Ferro Supremo, a formulation of liposomal iron enriched with vitamins and micronutrients (FS) compared to FeSO 4 in the presence of vitamin C. To achieve this goal, a differentiated Caco-2 cell has been used as a standard and worldwide preclinical model used for assessing the in vitro bioavailability and safety of different xenobiotics, including food and/or food supplements [ 25 , 26 ] and iron supplements [ 27 ]. In particular, preliminary experiments suggested that FS is not able to severely affect the viability of Caco-2 cells measured by MTT.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it is quite important to have new iron formulations that show better safety and efficacy than standard ones. In this context, our results clearly demonstrated the safety and the trans-epithelial transported efficacy of Ferro Supremo, a formulation of liposomal iron enriched with vitamins and micronutrients (FS) compared to FeSO 4 in the presence of vitamin C. To achieve this goal, a differentiated Caco-2 cell has been used as a standard and worldwide preclinical model used for assessing the in vitro bioavailability and safety of different xenobiotics, including food and/or food supplements [ 25 , 26 ] and iron supplements [ 27 ]. In particular, preliminary experiments suggested that FS is not able to severely affect the viability of Caco-2 cells measured by MTT.…”
Section: Discussionmentioning
confidence: 94%
“…The reaction was stopped by rinsing the sections in PBS. The sections were analyzed using an Eclipse 55i microscope equipped with a DS-L1 camera (Nikon, Tokyo, Japan) [23,24].…”
Section: Nadh Dehydrogenase Histochemistrymentioning
confidence: 99%